Critical analysis of awareness campaigns against gender violence in Mexico 2020 - Ruiz, Zennia (UNIVERSIDAD DE SONORA, 2023)
in Mexico, gender violence is detected as a systemic and structural problem that requires the intervention of various disciplinary visions to attend to and reduce the number of victims. Among the strategies are the campaigns developed by designers and visual communicators in public, private and institutional institutions. governmental. However, such strategies have been found to expose inconsistent messages. To illustrate this statement, the visual elements, and the type of message of three audiovisual campaigns developed in Mexico in 2020 will be examined: #Cuenta hasta 10 (Segob), #Noestássola (SpotlightMX) and #No EstásSola (Segob) through a model of analysis from a position of critical feminism. The results highlight the incomplete discourse within the campaigns, since it shows a repetition of stereotypes around the different types of aggression, as well as the role that women have within the home.